Conceptualizing a Model for Adoption of Online Social Networks as a Learning Tool - Mufadhal, Mokhtar Esmail; Noor Azida, Sahabudin; Al-Sharafi, Mohammed A. (American Scientific Publisher, 2018)
Online Social Networks (OSNs) are being used by most students, and more educational institutes are adopting OSNs in facilitating the learning activities. However, before implementation a new technology, the identification and measurement of factors affecting users’ acceptance of the new technology is critical to predict the success or failure of that technology. This research work provides a theoretical and conceptual model based on Technology Acceptance Model (TAM) and an online survey of 26 undergraduate students were collected for the preliminary data to assess the proposed model. The results of this study have significant implications and considerable value for higher educational institutes to devise better strategies for adoption of OSNs’ as a learning tool.